Kneading Techniques And Deep Breathing Relaxation Against Pain Reduction In First Time Maternity - Yohana Putri Apryanti (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Labor pain is a complex phenomenon with sensory, emotional and perceptive components and is considered one of the most serious types of pain. Severe pain can affect the increase in heart rate, respiratory system, increase in blood pressure and can cause stress and inhibit the release of the hormone oxytocin which results in inadequate contractions and disruption of cervical dilatation. The aim of the study was to assess the effectiveness of the kneading technique and deep breathing relaxation on pain intensity during the first active phase in labor mothers. This research method is a quasi experiment using the two groups post test only design method. The sampling technique was a purposive sample of 40 people divided into 20 respondents in the intervention group and 20 respondents in the control group and the duration of the study was 7 months. Data analysis consisted of bivariates with Mann Whitney. The results showed that the intensity of labor pain in the group given the kneading technique and deep breathing relaxation for mothers in labor showed a mild pain scale of 11 people (55%). The intensity of labor pain in the non-treated group showed a severe pain scale of 18 (90%). Conclusion: There is an effect of kneading techniques and deep breathing relaxation on the intensity of labor pain in the first active phase of labor in women with a p-value less than 0.0000.Abstrak: Nyeri persalinan adalah fenomena yang kompleks dengan komponen sensorik, emosional  dan perseptif dan dianggap sebagai salah satu jenis nyeri yang paling serius. Rasa nyeri yang hebat dapat mempengaruhi kenaikan denyut, sistem pernafasan, kenaikan tekanan darah dan dapat menyebabkan stress dan menghambat pengeluaran hormon oksitosin yang berakibat kontraksi tidak adekuat dan terganggunya dilatasi serviks. Tujuan penelitian untuk menilai efektivitas teknik kneading dan relaksasi nafas dalam terhadap intensitas nyeri kala I fase aktif pada ibu bersalin. Metode Penelitian ini Quasi experiment dengan metode two groups post test only design. Teknik pengambilan sampel yaitu purposive sample sebanyak 40 orang yang terbagi menjadi 20 responden pada kelompok intervensi dan 20 responden pada kelompok kontrol dan lama penelitian dilakukan selama 7 bulan. Analisis data terdiri dari bivariat dengan Mann Whitney. Hasil penelitian menunjukkan bahwa Intensitas nyeri persalinan pada kelompok yang diberikan teknik kneading dan relaksasi nafas dalam pada ibu bersalin menunjukkan skala nyeri ringan sebanyak 11 orang (55%). Intensitas nyeri persalinan pada kelompok yang tidak diberikan terapi menunjukkan skala nyeri berat sebanyak 18 (90%). Kesimpulan: Ada pengaruh teknik kneading dan relaksasi nafas dalam terhadap intensitas nyeri persalinan kala I fase aktif pada ibu bersalin dengan nilai p-value kurang dari 0,0000